Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

From micro to mesoscale: Understanding the influence of macroalgal communities on Ostreopsis Schmidt blooms - M. Monserrat; V. Asnaghi; J. Verdura; L. Meroni; R. Lemée; A.M. Rossi; G. Romero; F. Priouzeau; M. Chiantore; L. Mangialajo (Harmful Algae, 2024)

Considerations on using MCS and EMS-98 macroseismic scales for the intensity assessment of contemporary Italian earthquakes - S. Del Mese; L. Graziani; F. Meroni; V. Pessina; A. Tertulliani (Bulletin of Earthquake Engineering, 2023)
The concept of macroseismic intensity arose with the purpose of measuring the strength of an earthquake by the effects it causes on buildings, people, and domestic furnishings. From this perspective, buildings can be considered seismic sensors that record the shaking. Early scales were conceived at a time when buildings were mainly in masonry and therefore they could be used as markers of the intensity in case of earthquakes. Indeed, since they were fairly homogeneous, their level of damage could be considered as an indicator of the shaking level. In recent decades, the evolution of construction techniques have made the MCS scale unsuitable for damage assessment of buildings of various resistance. To overcome this problem the EMS-98 scale was designed. Because the MCS scale is still used in Italy, even in the presence of many reinforced concrete buildings, the purpose of this work is to show that the EMS-98 is the most suitable tool for assessing intensity as it is more consistent with the built environment. Theoretical and real intensity assessments, by both MCS and EMS-98, have been determined and compared, showing that nowadays intensity is a function of the vulnerability. MCS and EMS-98 would be comparable only when the building stock is composed of very vulnerable edifices (generally class A). Finally, thanks to the similarity of the two scales for old and vulnerable buildings, EMS-98 appears fully adequate to investigate historical earthquakes and represents a powerful tool to ensure continuity among earthquakes of different epochs.

PPARγ activation regulates lipid droplet formation and lactate production in rat Sertoli cells - A. Gorga; G. M. Rindone; M. Regueira; E. H. Pellizzari; M. C. Camberos; S. B. Cigorraga; M. F. Riera; M. N. Galardo; S. B. Meroni (Cell and Tissue Research, 2017)

Building vulnerability and seismic risk analysis in the urban area of Mt. Etna volcano (Italy) - S. D’Amico; F. Meroni; M. L. Sousa; G. Zonno (Bulletin of Earthquake Engineering, 2016)

The role of the urban system dysfunction in the assessment of seismic risk in the Mt. Etna area (Italy) - F. Meroni; G. Zonno; R. Azzaro; S. D’Amico; T. Tuvè; C. S. Oliveira; M. A. Ferreira; F. Mota de Sá; C. Brambilla; R. Rotondi; E. Varini (Bulletin of Earthquake Engineering, 2016)

Assessing Seismic Damage Through Stochastic Simulation of Ground Shaking: The Case of the 1998 Faial Earthquake (Azores Islands) - G. Zonno; C. S. Oliveira; M. A. Ferreira; G. Musacchio; F. Meroni; F. Mota-de-Sá; F. Neves (Surveys in Geophysics, 2010)

Declining Incidence of AIDS and Increasing Prevalence of AIDS Presenters Among AIDS Patients in Italy - B. Castelnuovo; E. Chiesa; S. Rusconi; F. Adorni; M. Bongiovanni; S. Melzi; P. Cicconi; F. Tordato; L. Meroni; T. Bini; A. d’Arminio Monforte (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

The SERGISAI procedure for seismic risk assessment - G. Zonno; M. García-Fernández; M.J. Jiménez; S. Menoni; F. Meroni; V. Petrini (Journal of Seismology, 2003)

Seismic Risk Evaluation - F. Meroni; G. Zonno (Surveys in Geophysics, 2000)

Comparative mapping of Xp22 genes in hominoids – evolutionary linear instability of their Y homologues - B. Gla¨ser; F. Gru¨tzner; K. Taylor; K. Schiebel; G. Meroni; K. Tsioupra; J. Pasantes; W. Rietschel; R. Toder; U. Willmann; S. Zeitler; P. Yen; et al. (Chromosome Research, 1997)